2004
DOI: 10.1074/jbc.m311633200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Glycosaminoglycan Recognition Element of the C Chemokine Lymphotactin

Abstract: Chemokine-mediated recruitment of leukocytes in vivo depends on interactions with cell surface glycosaminoglycans. Lymphotactin, the unique member of the "C" chemokine subclass, is a highly basic protein that binds heparin, a glycosaminoglycan, with high affinity (ϳ10 nM). We detected lymphotactin-heparin binding by NMR and mapped this interaction to a narrow surface that wraps around the protein. Substitutions in and around this binding site and surface plasmon resonance analysis of heparin binding affinity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 46 publications
2
78
0
Order By: Relevance
“…Like other chemokines (16), Ltn binds heparin with high affinity, and its in vivo activity depends on GAG interactions (17). Wild-type Ltn elutes from a heparin-Sepharose column in two distinct fractions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Like other chemokines (16), Ltn binds heparin with high affinity, and its in vivo activity depends on GAG interactions (17). Wild-type Ltn elutes from a heparin-Sepharose column in two distinct fractions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data could indicate that very little soluble XCL1 is released into the ascitic fluid. Thus, likely sources of XCL1 in the peritoneal cavity include areas in the vicinity of the XCL1-producing cells of the immune system, ovary, and other peritoneal organs as well as cell surface-attached GAGs harboring XCL1 (13,30,31). To further investigate the possible source of XCL1 in EOC, we tested the EOC cell lines IGROV-1, SKOV-3, and A2780 and found that XCL1, but not XCL2, RNA is expressed by these EOC cell lines (Fig.…”
Section: Xcl1 and Xcl2 Are Present In Eoc Ascites And Cell Linesmentioning
confidence: 99%
“…Heparin and HS are closely related, overlapping structures that are widely distributed in invertebrates (Medeiros et al, 2000;Nobuo, 2003;Cesaretti et al, 2004), as well as in vertebrates (Gomes and Dietrich, 1982). Moreover, HS GAGs modulate many biological activities including signal transduction (Ibrahimi et al, 2005), inflammation (Peterson et al, 2004), complement activation (Yu et al, 2005) and cAMP-dependent substrate phosphorylation catalyzed by protein kinase (Dittmann et al, 1998). Some of the biological roles of GAGs have been exploited for the design and preparation of therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%